Pregnancy and uterine fibroids (leiomyoma): a critical review - I. F. Fatkullin; Yu. V. Orlov; L. S. Fatkullina; V. V. Korennaya (Фундаментальная и клиническая медицина)
Here we review current opportunities in pregnancy management in women with uterine fibroids, also known as leiomyoma. Uterine fibroids are associated with a number of complications already at planning for pregnancy and also during pregnancy and labour. We discuss vaginal delivery and caesarian section in such patients, considering safety issue with regards to myomectomy and its expediency before pregnancy and during caesarean section. Multiple controversies and debates emphasize the need for the further research in this direction.